RELASI SOSIAL MAHASISWA PENGHUNI LAMA DENGAN PENGHUNI BARU DI ASRAMA PUTRA KABUPATEN KUBU RAYA - Samudro, Joko; Bahari, Yohanes; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe thesis is titled The Social Relation of old residents with new residents in Kubu Raya District dormitory. The method of this research is used a descriptive method with a qualitative research form. The resources of this research data is the old residents, new residents, and the dormitory managers of Kubu Raya district. The data collection techniques in this research are through observation, interviews, and documentation. The data collection tools used are observation guides, interview guides and documentation tools. The analysis in this study was presented in a qualitative descriptive by using informant as many as 5 peoples. The problem in this thesis is how the student social relations of old residents with new residents in Kubu Raya District dormitory. Sub problem 1. What are the social relations of old resident with the new resident? 2. What is the factors of social relations between old and new residents is happened? The results of this study proved that the old residents with the new residents were well connected with each other's attitude and mutual respect among their fellow residents in the dorm. Relationship with the old resident with new resident can be happened a good cooperation in the form of action and communication well, even though each person has a different character but can be a unity that can foster a sense of A family of high sympathy and empathy.Â Keywords: Social Relations, Students, Son Dormitory Residents